Demonstrating quantum random with single photons - Bronner, Patrick; Strunz, Andreas; Silberhorn, Christine; Meyn, Jan-Peter (European Journal of Physics, 2009)
We present an experiment for education which demonstrates random transmission or reflection of heralded single photons on beam splitters. With our set-up, we can realize different quantum random experiments by appropriate settings of polarization rotators. The concept of entanglement is motivated by correlated randomness. The experiments are suitable for undergraduate education and are available as interactive screen experiments. © 2009 IOP Publishing Ltd.
UnivIS-Import:2015-03-09:Pub.2009.nat.dphy.PI.PDP.demons